MODEL PEMBELAJARAN KESEIMBANGAN DALAM PENJAS MELALUI PENDEKATAN LINGKUNGAN PERSAWAHAN PADA SISWA KELAS III SD NEGERI 06 TERBAN KECAMATAN JEKULO KABUPATEN KUDUS TAHUN 2013 (Department of Physical Education, Sport, Health and Recreation, 2014)
The purpose of this study to produce a learning model approach to environmental balance through the ricefields in Elementary School third-grade students in learning Penjasorkes Terban 06. This study is a researchmethod development. The product development procedures include product analysis, develop initial products,expert validation and revision, testing and revision small groups, large groups and testing the final product.The data analysis technique used is descriptive percentages. Data results of the student questionnaire on a smalltest group gained an average percentage of 89.72% with the answer to both categories and the results of testingthe student questionnaire answers with the large group obtained 83.61% percentage. with both categories.Students had no difficulty when playing motion balance approach paddy environment. Based on the researchdata, it was concluded that the balance of the learning environment through rice fields and effective approachaccording to the characteristics of students that can be used in learning Penjasorkes.